Synthetic and Mechanistic Studies on Pd(0)-Catalyzed Diamination of Conjugated Dienes - Zhao, Baoguo; Du, Haifeng; Cui, Sunliang; Shi, Yian (Journal of the American Chemical Society, 2010)
Various dienes and a triene can be regioselectively diaminated at the internal double bond with good yields and high diastereoselectivity using di-tert-butyldiaziridinone (5) as the nitrogen source and Pd(PPh3)4 (1−10 mol %) as the catalyst. Kinetic studies with 1H NMR spectroscopy show that the diamination is first-order in total Pd catalyst and inverse first-order in PPh3. For reactive dienes, such as 1-methoxybutadiene (6g) and alkyl 1,3-butadienes (6a, 6j), the diamination is first-order in di-tert-butyldiaziridinone (5) and zero-order in the olefin. For olefins with relatively low reactivity, such as (E)-1-phenylbutadiene (6b) and (3E,5E)-1,3,5-decatriene (6i), similar diamination rates were observed when 3.5 equiv of olefins were used. Pd(PPh3)2 is likely to be the active species for the insertion of Pd(0) into the N−N bond of di-tert-butyldiaziridinone (5) to form a four-membered Pd(II) complex (A), which can be detected by NMR spectroscopy. The olefin complex (B), formed from intermediate A via ligand exchange between the olefin substrate and the PPh3, undergoes migratory insertion and reductive elimination to give the diamination product and regenerate the Pd(0) catalyst.